Comparison of histochemical methods for the histological analysis of human gingival samples - Victor Hugo Simancas Escorcia; Jocsan Leal Betancur; Antonio Díaz Caballero; Jennifer Orozco Páez (Editorial Ciencias Médicas, 2021)
Introduction: Histological staining techniques are useful in the ultrastructural analysis of tissue samples, including gingival tissue. Objective: Compare the usefulness of three histochemical methods (hematoxylin-eosin, Masson-Goldner and sirius red) for identification of cellular elements and other constituents of gingival tissue. Methods: An in vitro experimental study was conducted which included the analysis of gingival tissue from healthy donors without gingival inflammation signs and indication of periodontal surgery. The gum samples were obtained by gingivectomy, processed with paraffin, cut with a microtome and placed on Polysine adhesion slides. The samples were grouped, stained with hematoxylin-eosin, Masson Goldner and sirius red, and visualized under a Leica DM 750® microscope. Reading of the findings was performed by oral pathologists. Results: Hematoxylin-eosin staining found cellular and extracellular elements of the epithelial and connective tissue: violet-blue nuclei, pink cytoplasms, light rose collagen fibers, and arterioles and venules with differentiated tunica adventitia, media and intima. Masson-Goldner staining differentiated purple nuclei and fuchsia cytoplasm. It displayed specificity identifying green collagen fibers with dense, homogeneous and parallel distribution in the gingival connective tissue. Sirius red staining allowed identification of bright rose collagen fibers, whereas epithelial tissue and blood vessels were yellow. Conclusion: Each of the histological staining methods evaluated in the study shows a certain affinity with and sensitivity to cellular structures and components of the specific extracellular matrix. All three are useful for the study of gingival tissue and could contribute to the analysis of gingival biopsies.